American founding son : John Bingham and the invention of the Fourteenth Amendment - Magliocca, Gerard N. (UPCC book collections on Project MUSE., 2013)
A leading antislavery lawyer and congressman from Ohio, John Bingham wrote the most important part of the Fourteenth Amendment to the Constitution, which guarantees fundamental rights and equality to all Americans. Drawing on his personal letters and speeches, this book traces his life from his roots in Pennsylvania through his career as a leader of the Republican party.